2013
DOI: 10.1007/s10815-013-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Chinese men undergoing different assisted reproductive technique treatments: prevalence and risk factors

Abstract: Purpose To explore the prevalence and risk factors for depression in men undergoing different assisted reproductive technique (ART) treatments in Chinese population. Method This was a prospective study of 844 men undergoing ART treatments. All men were distributed to four groups, according to they received treatments. The treatments included IUI (intrauterine insemination), IVF(in vitro fertilization), ICSI(intra cytoplasmatic sperm injection) and TESA/PESA (percutaneous epididymal sperm aspiration/testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
4
1
Order By: Relevance
“…Major depression with rate of 42.6% was prevalent in our study. This rate is higher than results from previous research conducted in Sweden ( 15 , 26 , 27 ), China ( 12 , 28 , 29 ), Italy ( 13 ) and in Iran ( 22 ). Possible explanation could be attributed to application of various instruments to determine prevalence of depression; in some countries, Mental Health Inventory–5 and modified version of the PRIME-MD PQ were used.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Major depression with rate of 42.6% was prevalent in our study. This rate is higher than results from previous research conducted in Sweden ( 15 , 26 , 27 ), China ( 12 , 28 , 29 ), Italy ( 13 ) and in Iran ( 22 ). Possible explanation could be attributed to application of various instruments to determine prevalence of depression; in some countries, Mental Health Inventory–5 and modified version of the PRIME-MD PQ were used.…”
Section: Discussioncontrasting
confidence: 71%
“…Duration of marriage is a significant predictor for occurrence of depression as Chinese reports similarly confirm this finding ( 28 , 30 , 31 ). However, different results were obtained by a Chinese study carried out by Yang et al ( 12 ) and another study in Turkey ( 32 ).…”
Section: Discussionsupporting
confidence: 61%
“…The studies were conducted in 9 high-income and 13 low- and middle-income countries. One study used Mini International Neuropsychiatric Interview (MINI) [ 20 ], 3 studies the Depression Anxiety Stress Scales (DASS) [ 14 , 32 , 40 ], one study the Center of Epidemiologic Studies Short Depression Scale (CES-D) [ 31 ], one study the Mental Health Inventory–5 (MHI-5) [ 38 ], one study Depression Scale (D-S) [ 28 ], 3 studies the Zung Self-Rating Depression Scale (ZDS) [ 33 , 37 , 41 ], 4 studies the Hospital Anxiety and Depression Scale (HADS) [ 26 , 27 , 36 , 42 ] and 8 studies the Beck Depression Inventory (BDI) [ 21 25 , 29 , 34 , 39 ] to identify depression (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 ] Li et al ., in a study conducted in China, reported idiopathic factor as the most common cause for infertility (43.9%), while female factor (20.8%), male factor (20.3%), and combined factor (15%) were ranked after that, respectively. [ 16 ] Direkavand Moghadam et al ., in thier meta-analysis study, reported an equal rate for male and female factors of infertility. [ 17 ] With regard to the aforementioned studies, it is found that the prevalence of infertility has been reported differently in various studies.…”
Section: Discussionmentioning
confidence: 99%